P-body loss is concomitant with formation of a messenger RNA storage domain in mouse oocytes - Flemr, Matyas; Ma, Jun; Schultz, Richard M; Svoboda, Petr (Biology of reproduction, 2010)
In mammalian somatic cells, several pathways that converge on deadenylation, decapping, and 5'-3' degradation are found in cytoplasmic foci known as P-bodies. Because controlled mRNA stability is essential for oocyte-to-zygote transition, we examined the dynamics of P-body components in mouse oocytes. We report that oocyte growth is accompanied by loss of P-bodies and a subcortical accumulation of several RNA-binding proteins, including DDX6, CPEB, YBX2 (MSY2), and the exon junction complex. These proteins form transient RNA-containing aggregates in fully grown oocytes with a surrounded nucleolus chromatin configuration. These aggregates disperse during oocyte maturation, consistent with recruitment of maternal mRNAs that occurs during this time. In contrast, levels of DCP1A are low during oocyte growth, and DCP1A does not colocalize with DDX6 in the subcortical aggregates. The amount of DCP1A markedly increases during meiosis, which correlates with the first wave of destabilization of maternal mRNAs. We propose that the cortex of growing oocytes serves as an mRNA storage compartment, which contains a novel type of RNA granule related to P-bodies.
Keywords: buněčná diferenciace; myši; vztahy mezi strukturou a aktivitou; Ovary; Multiprotein Complexes; oocyty; trans-aktivátory; Mice, Inbred C57BL; Animals; konformace proteinů; ovarium; proteiny vázající RNA; Intracellular Space; RNA Caps; ribonukleoproteiny; Mice; myši inbrední C57BL; Gene Expression Regulation, Developmental; Endoribonucleases; Female; vývojová regulace genové exprese; RNA-Binding Proteins; ženské pohlaví; Cell Differentiation; multiproteinové komplexy; zvířata; Trans-Activators; intracelulární prostor; endoribonukleasy; RNA messenger skladovaná; Oocytes; cytoplazmatická granula; Ribonucleoproteins; Cytoplasmic Granules; RNA, Messenger, Stored; Structure-Activity Relationship; Protein Conformation; RNA čepičky